ANALYSIS OF THE USE OF ACCOUNTING INFORMATION AND APPLICATION OF FINANCIAL ACCOUNTING STANDARDS OF SMALL AND MEDIUM ENTERPRISES (SAK EMKM) IN FISHERIES MSMES IN NUSA TENGGARA TIMUR (Case study at Al-Ijtihad MSMEs in Kupang City) - Cahyaningtias Cahyaningtias; Fauziyah Lamaya (JASS (Journal of Accounting for Sustainable Society), 2022)
One of the MSME sectors that many people in Kupang are engaged in is fisheries. However, some fisheries MSMEs have not succeeded in developing their businesses to a larger scale. The use of accounting information is one of the factors that affect the level of business success and SAK EMKM is a financial accounting standard for MSMEs. This study aims to determine the use of accounting information in business activities at Al-Ijtihad SMEs and the application of SAK EMKM in the presentation of its financial statements. the type of qualitative research with research design is case study. The results showed that the use of accounting information at Al-Ijtihad MSMEs was well implemented, for the type of operating accounting information, while for the type of management and financial accounting information it had not been fully implemented. SAK EMKM has also not been implemented at all in Al-Ijtihad MSME business activities.